2005
DOI: 10.2143/ac.60.1.2005049
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular changes in mucopolysaccharidoses in Taiwan

Abstract: From 1991 to 2002, we managed 72 patients with mucopolysaccharidoses. We retrospectively reviewed the records of 37 for whom detailed physical findings and cardiovascular evaluation were available. Twenty patients had serial electrocardiographic (ECG) examinations, and none had arrhythmias. All 20 patients had low R wave voltage in V6. One type VI patient had ischaemic changes secondary to severe cardiomyopathy at the terminal stage of her disease. Among the 37 patients in whom echocardiography was performed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 10 publications
2
25
0
4
Order By: Relevance
“…3c. Although the diffraction pattern was not on a zone axis due to the single tilting nature of the TEM holder, a clear 4H-SiC related diffraction feature [36] was observed. At the dark cluster regions indicated by dotted arrows in Fig.…”
Section: Resultsmentioning
confidence: 96%
“…3c. Although the diffraction pattern was not on a zone axis due to the single tilting nature of the TEM holder, a clear 4H-SiC related diffraction feature [36] was observed. At the dark cluster regions indicated by dotted arrows in Fig.…”
Section: Resultsmentioning
confidence: 96%
“…The signs of ventricular hypertrophy on ECG recordings may be less common than the hypertrophy diagnosed using echocardiographyin the corresponding patients since the GAGs are electrically less conductive [24]. This electrical conduction impairing property of GAGs together with increased anterior-posterior diameter of the chest may be the cause of low voltage R wave in V6 in MPS VI patients [9]. Other abnormalities like non-specific T-wave abnormalities, precordial inverted T waves, ST depression, premature ventricular extrasystoles and supraventricular tachyarrhythmias (atrial flutter) have also been reported [9,25,26].…”
Section: Electrocardiogram Characteristicsmentioning
confidence: 99%
“…Clinical features include short stature, coarse facial features, stiff joints, skeletal malformations (dysostosis multiplex), respiratory and cardiovascular disorders, corneal clouding, and hepatosplenomegaly. Cardiac impairment representing a serious clinical problem in MPS VI [5], leads to increased morbidity and premature mortality in affected patients [5][6][7][8][9][10].…”
Section: Clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…All these studies allow assumptions, derived from these observation, but concrete analysis of atrial contractility in patients with MPS are missing. The importance of MPS for cardiac contractility can be seen in a study of Chen, who examined 27 boys (age 2-11 years) with Hunter syndrome: only 5 patients had normal echocardiographic and/or autopsy results, 19 had changes in mitral valve, 5 had changes in aortic valve and 10 patients had already signs of heart disease [13]. So MPS does not only affect cardiac heart valves, but also the whole cardiac contractility.…”
Section: Discussionmentioning
confidence: 99%